(untitled) (Studia Universitatis Vasile Goldiș Arad, Seria Științe Economice, 2018)
The performance guarantee represents the contractor’s liability to ensure the beneficiary on the fulfillment of the quality conditions for the contracted works, as well as of their execution within the agreed contractual term. In the context of a growth trend in the industrial construction market since 2018, we considered it appropriate to study the impact of the performance guarantees on the financial balance of the contractors operating on this market. Through this research we aim to analyze the methods of guaranteeing the construction works, to assess the financial, accounting and fiscal issues of a construction company as a general contractor, to identify potential risks and to find solutions to avoid them.